LIFE AFTER DEATH: In the Intertestamental Palestine Context - Terrence, Xavier (Journal of Dharma, 2012)
The intertestamental history of the people of Israel, the Jews, marked a new kind of identity, an identity amidst the silence of God. The humiliating experience of slavery and their acquaintance with the foreign culture, religion and philosophy had its own influence on them. This was further aggravated by the Hellenistic and Roman culture and philosophy through invasions. In addition, there was no new revelation from God. This experience made a great impact in their understanding of life and death: while looking for a survival in terms of nation as a whole, they tried also to see a survival beyond death in the form of resurrection. This new climate of religious and philosophical thinking and expression favoured Jesus and the early Church towards quite a new understanding of life, death and afterlife. Most of these writings are of apocalyptic nature. A word on apocalyptic, the Child of Prophecy,would surely help us to understand its importance.